2010
DOI: 10.1038/ajg.2009.715
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Hepatocellular Carcinoma: What Role Does Diabetes Have in the Presence of Other Known Risk Factors?

Abstract: Known risk factors for hepatocellular carcinoma (HCC) include hepatitis C, hepatitis B, and alcoholic liver disease. Several studies have examined diabetes as a risk factor for HCC because of its association with fatty liver disease and nonalcoholic steatohepatitis. The current study by Tung et al. found that neither diabetes nor overweight was a risk factor for HCC. Results were consistent using both a cross-sectional and a case -control study approach. Findings from this study suggest that diabetes and overw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A recent finding has demonstrated that genes involved in the lipid metabolism are crucial in cell transformation and over-expressed in tumor tissues [36]. Diabetes and non-alcoholic fatty liver disease may significantly increase the risk of developing HCC when other risk factors, such as hepatitis B virus, are present [37]. It is speculated that metabolic diseases, such as diabetes mellitus, and cancer may share common disrupted metabolic pathways [36].…”
Section: Discussionmentioning
confidence: 99%
“…A recent finding has demonstrated that genes involved in the lipid metabolism are crucial in cell transformation and over-expressed in tumor tissues [36]. Diabetes and non-alcoholic fatty liver disease may significantly increase the risk of developing HCC when other risk factors, such as hepatitis B virus, are present [37]. It is speculated that metabolic diseases, such as diabetes mellitus, and cancer may share common disrupted metabolic pathways [36].…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why high ALT levels were negatively associated with screening, though this effect was not observed among cirrhotic patients who attended liver subspecialty clinic. Limited studies have shown that noncirrhotic hepatitis B-infected Asians are less frequently screened for HCC compared to cirrhotics, and patients seen by gastroenterologists or hepatologists are more likely to receive regular HCC screening, with higher rates of screening rates reported among gastroenterologists compared to internists or family practitioners [13,19,21].…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD in those with T2D will follow a worse prognosis via hastened progression to NASH, liver cirrhosis and its complications and increased risk of developing NAFLD-HCC[ 43 , 207 - 210 ]. Specularly, concurrent NAFLD will often worsen the course of T2D[ 211 ].…”
Section: Nafld and T2d: A Dangerous Combinationmentioning
confidence: 99%